Respons Hasil Padi dan Hara Tanah Sawah terhadap Bakteri Pelarut Fosfat dan Pemfiksasi Nitrogen - Muhimmatul Husna; Sugiyanta Sugiyanta; Etty Pratiwi (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2021)
The condition of unfertile paddy field due to excessive inorganic fertilizer application causing soil degradation. Fertilizing techniques using phosphate solubilizing and nitrogen fixer bacteria are breakthroughs that should be developed in paddy cultivation to increase fertility soil and harvest of rice. This research aims to study on phosphate solubilizing and nitrogen fixer bacteria ability to increase the harvest of rice by increasing chemical and biological fertility of soil. The research was conducted in the greenhouse of Sawah Baru experimental garden, IPB University. The design used was a completely randomized design with one factor that was dosage of inorganic fertilizers (NPK) with seven levels that were control, NPK 100%, NPK 0% + bacteria, NPK 25% + bacteria, NPK 50% + bacteria, NPK 75% + bacteria and NPK 100% + bacteria. Each stage was repeated four times, so there were 28 units. The results of phosphate solubilizing and nitrogen fixer bacteria could produce more rice grain 0.32 ton.ha-1 than NPK 100% (recommended dose). Biological soil fertility improved with the increased population of bacteria, but there was no improved soil chemical fertility of soil.